Probing the generality of spin crossover complex T½vs. ligand 15N NMR chemical shift correlations: towards predictable tuning. Issue 22 (5th October 2021) - Bondì, Luca; Rodríguez-Jiménez, Santiago; Feltham, Humphrey L. C.; Garden, Anna L.; Brooker, Sally
Abstract : A study of 6 families (42 members) demonstrates that within a family the easily calculated 15 N-NMR values of ligands enable predictable tuning of T1/2 in the corresponding complexes, except for 2 families with weakly influencing meta -substituents. Abstract : Four new bidentate 5-(Z -pyridine)-4-(4-methyl-phenyl)-3-phenyl-1, 2, 4-triazole ligands L pytZ ( meta -Z = CF 3, Br, F, Me ) and the corresponding family of [Fe II ( L pytZ )2 (NCBH3 )2 ] complexes, in addition to the literature unsubstituted analogue [Fe II ( L pytH )2 (NCBH3 )2 ], are prepared and studied herein. Single crystal structure determinations on all four new complexes confirmed the expected octahedral coordination, with trans -NCBH3 co-ligands. Solid-state variable temperature magnetic studies of air-dried crystals showed that [Fe II ( L pytCF 3 )2 (NCBH3 )2 ] is SCO active with a hysteresis loop at 208 K ( T 1/2 ↓ = 203 K, T 1/2 ↑ = 213 K; Δ T 1/2 = 10 K); [Fe II ( L pytBr )2 (NCBH3 )2 ] is not SCO active until heated above RT, while [Fe II ( L pytF )2 (NCBH3 )2 ] and [Fe II ( L pytMe )2 (NCBH3 )2 ] are SCO active close to RT ( T 1/2 = 290 and 300 K respectively). Solution phase variable temperature Evans NMR method studies in CDCl3 showed that four of the complexes were SCO active close to RT ( T 1/2 = 279–294 K) whilst [Fe II ( L pytCF 3 )2 (NCBH3 )2 ] was mostly LS at RT ( T 1/2 ∼ 374 K). These solution phase T 1/2 values, and those for four literature families of bi- (five L azine ), tri- (fourteen bpp X, Y, twelve pybox X ) or tetra-dentate (seven pytacn X ) ligands, which feature para (X ) pyridine or meta (Y ) pyrazole ring substituents, are used, along with the calculated 15 N NMR chemical shift of the coordinating azine/azole nitrogen (N A ) in the ligand (for all forty-two ligands; using a refined protocol), to test the generality of the previously reported correlation of δ N A chemical shift in the free ligand with the solution T 1/2 for the respective iron(ii ) complex. Moderately good to excellent correlations of δ N A with T 1/2 were observed for each of the ligand families with a para substituent ( R 2 = 0.69–0.96), whereas there is no correlation when meta substituents are modified ( R 2 = 0.15–0.37), probably because the electronic impact of this is too small. Finally, δ N A also shows promise as an easily calculated measure of the electronic effect of any substituent, in contrast to the Hammett constant ( σ p + ) which is not available for all possible substituents.